Spitting out the demons: Extracellular vesicles in glioblastoma. Issue 2 (4th March 2017) - André-Grégoire, Gwennan; Gavard, Julie
ABSTRACT: Discovered decades ago, extracellular vesicles (EVs) emerge as dedicated organelles, able to deliver protected, specific cellular cues throughout the organism. While virtually every cell can release EVs, cancer cells co-opted this feature and efficiently unleashed them both in the tumor microenvironment and toward healthy tissues. This might contribute to tumor aggressiveness and spreading. Cancer-derived EVs that contain DNA, mRNA, miRNA, and packed and transmembrane proteins can operate locally or at distance. This review will focus on the high-grade brain tumor (i.e. glioblastoma)-derived EVs, discussing recent reports on i) their phenotype and content, ii) their putative functions, and iii) their clinical potential for improving diagnosis and therapeutics.